Pharmacokinetics and bioavailability of ofloxacin following single intramuscular and subcutaneous administration in goats - YADAV, RAJKUMAR SINGH; GARG, SATISH KUMAR (The Indian Journal of Animal Sciences, 2016)
Comparative disposition kinetics of ofloxacin following intramuscular (i.m.) and subcutaneous (s.c.) administration was studied in goats @ 10 mg/kg. Ofloxacin was determined by HPLC method and kinetic parameters using a software. Appreciable plasma concentrations were observed within 2.5 min of drug administration and peaked at 1 h. t1/2ka and t1/2β values were 13.59 and 78.41 min after i.m. administration while 17.89 and 103.59 min after s.c. administration and the corresponding bioavailability values were 75.43±5.00 and 102.07±7.00 %. Ofloxacin may be adiministered to goat @10 mg/kg at 12 h interval by s.c. route.